Smart Lecture Video Production: A Case Study with Philosophy and Media Literacy* - Kondo, Tomotsugu (International Journal on Open and Distance e-Learning, 2017)
This paper describes a case study of a method of creating video lectures while reducing cost and improving quality. Since 1985, the Open University of Japan (OUJ) has provided TV and radio broadcast lectures, as well as face-to-face lectures. As an additional lecture style, full online courses were launched in 2016. I was appointed start-up project manager, so I developed the Smart Lecture Video Production method to prepare the online courses. Our mission was to develop six undergraduate courses and two graduate courses within a year. Because hiring a video crew is generally expensive, we decided to try the entire development process ourselves. However, the project faced many problems, such as a limited budget, tight deadlines and lack of staff. To solve these problems, I created the following philosophy: we will achieve this project for all learners, for lecturers and staff. In accordance with this philosophy, we also developed production tools and media literacy instructional materials. As a result, the project mission was accomplished. Currently, the Smart Lecture Video Production method is applied to not only online courses but also some TV broadcasting productions.